A Time to Build : Does TA Matter for Revenue Mobilization?. (IMF Working Papers; Working Paper ;, 2021)
We use a unique data set for 115 countries, from 2000-18, and 5-year non-overlapping averages to explore the impact of technical assitance on revenue mobilization. To the authors' knowledge this is the first such effort to determine a direct relationship between technical assistance and the improvement in tax revenues. The paper finds that technical assistance significantly and positively increases tax revenues. Both income per capita and openness were found to positively improve the tax ratio in line with findings in the literature. Dynamic estimations also uncovered a long-run relationship among technical assistance, income per capita, openness, and tax revenues. This result further underscores that it takes time to build capacity and institutional resilience.